2011
DOI: 10.1002/chem.201102268
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Engineering through Temperature‐Induced Chemical Modification of 2H‐Tetraphenylporphyrin on Ag(111): Flat Phenyl Conformation and Possible Dehydrogenation Reactions

Abstract: Scratching the surface: Formation of a monolayer of 2H-tetraphenylporphyrins (2H-TPP) on Ag(111), either by sublimation of a multilayer in the range 525-600 K or by annealing (at the same temperature) a monolayer deposited at room temperature, induces a chemical modification of the molecules. Rotation of the phenyl rings into a flat conformation is observed and tentatively explained, by using DFT calculations, as a peculiar reaction due to molecular dehydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
104
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 64 publications
(119 citation statements)
references
References 37 publications
14
104
1
Order By: Relevance
“…Instead, the planar structures built up considerable ring tension, resulting from the formation of four new five-membered rings. The total strain ranged from 175 to 200 kJ/mol, according to DFT calculations [373]. Similar observations were made for 2HTPP on Cu(1 1 1) [481] (cf.…”
Section: Reactive Structural Adaptationsupporting
confidence: 73%
See 2 more Smart Citations
“…Instead, the planar structures built up considerable ring tension, resulting from the formation of four new five-membered rings. The total strain ranged from 175 to 200 kJ/mol, according to DFT calculations [373]. Similar observations were made for 2HTPP on Cu(1 1 1) [481] (cf.…”
Section: Reactive Structural Adaptationsupporting
confidence: 73%
“…This type of reactive structural adaptation was first observed by Di Santo et al [372,373,377]. After thermal desorption of a 2HTPP multilayer from an Ag(1 1 1) surface between 525 K and 600 K, the remaining monolayer consisted of molecules in which both the porphin macrocycle and the phenyl rings were parallel to the surface, as indicated by NEXAFS measurements [373]. On the basis of electron energy loss spectra (EELS), which showed the disappearance of hydrogen atoms, and DFT calculations, this change was attributed to dehydrogenative C-C bond formation between the ortho-positions at the phenyl rings and adjacent positions at the porphyrin macrocycle.…”
Section: Reactive Structural Adaptationmentioning
confidence: 54%
See 1 more Smart Citation
“…As an alternative, a different intramolecular structure (either a conformational change or a structural change due to light-induced intramolecular reactions) could lead to a different organization, for example, owing to changes in the molecular recognition interactions governing the self-assembly process, as well to changes in the molecular size and/or shape. [55] To get a comparative insight into the structure of oblique and rectangular phases under the same tunneling conditions, we made a RT deposition of trans-TPP(NH 2 ) 2 on a sample partially precovered by the rectangular phase, as shown in Figure 3. The comparison of the small-scale images shows that in both phases the molecules display the so-called saddle shape, a characteristic contrast of the metal-free porphyrin macrocycle.…”
Section: à2mentioning
confidence: 99%
“…[55]. There, it is shown that high-temperature annealing induces a flat molecular conformation as a consequence of the generation of new arylÀaryl carbon bonds between the phenyl rings and the macrocycle.…”
Section: à2mentioning
confidence: 99%